Prediction of black, immature and sour defective beans in coffee blends by using Laser-Induced Breakdown Spectroscopy - Silva, Tiago Varão [UNESP]; Milori, Débora Marcondes Bastos Pereira; Neto, José Anchieta Gomes [UNESP]; Ferreira, Ednaldo José; Ferreira, Edilene Cristina [UNESP] (Elsevier, 2019)
One of the most important factors that interfere negatively in coffee global quality has been blends with defective beans, especially those called Black, Immature and Sour (BIS). The methods based on visual-manual estimation of defective beans have shown their inefficiency in coffee value chain for large-scale analysis. The lack of fast, accurate and robust analytical methods for BIS determination is still a research gap. Laser-Induced Breakdown Spectroscopy (LIBS) is a fast, low-cost and residue-free technique capable of performing multielemental determination and investigating organic composition of samples. In the present work, LIBS together with spectral processing and variable selection were evaluated to fit linear regression models for predicting BIS in blends. Models showed high capacity of prediction with RMSEP smaller than 3.8% and R2 higher than 80%. Most importantly, measurements are guided by chemical responses, which make LIBS-based methods less susceptible to the visual indistinguishability that occurs in manual inspections.
Keywords: BIS; Coffee quality; Defective beans; LIBS